STUDENTS' PERCEPTIONS OF QUIZIZZ AS A MEDIUM FOR GRAMMAR QUIZZES - Nurhayati Nurhayati; Aditia Hilmansyah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Abstract. This research aims to explore students’ perceptions of using Quizizz as a medium for grammar quizzes, particularly in learning the present continuous tense. In the 21st-century educational context, digital tools have transformed the learning environment, enabling students to access materials more independently and engage in student-centered learning experiences. Quizizz, as a game-based teknology platform, offers features such as instant feedback, leaderboards, and interactive quizzes that enhance students’ motivation and engagement. However, not all students adapt equally to technological tools, making it essential to investigate their perceptions. This study employed a descriptive quantitative method involving 32 eighth-grade students from SMP 2 Cimanggu in the academic year 2023/2024. The data were gathered using a Likert-scale questionnaire distributed via Google Form and analyzed through SPSS software. The validity and reliability tests confirmed that all 20 items in the questionnaire were valid (r = 0.544–0.739) and highly reliable (Cronbach's Alpha = 0.929). The findings revealed overall positive student perceptions of Quizizz. For example, in Q1, 75% of students selected “Strongly Agree,” and Q20 achieved the highest mean score (M = 4.53), reflecting enthusiasm and motivation. The overall average score across all items was 4.03 on a 5-point scale, indicating consistent approval. These results support the conclusion that Quizizz is seen as an effective, enjoyable, and motivating platform for grammar learning. This study highlights the potential of integrating game-based learning tools into classroom instruction to enhance student participation and improve English grammar proficiency